MOTIVASI MAHASISWA MENIKAH (Studi Kasus Mahasiswi Yang Menikah di UIN Suska Riau) - Dewi Ria Pratiwi; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Married Student Motivation (Research of Married Student at UIN Suska Riau), this study was conducted at UIN Suska Riau. The subjects in this study were 5 female students. The informant retrieval technique is by using purposive sampling technique. The method used is descriptive qualitative research method. The results of this study were that the marriage at the time of the study was initially viewed negatively by the community, but in my research it can be seen that marriage during the study period had a positive impact, so that students avoid promiscuity, be more awake and feel safe, have more useful time, start marriage from zero that can foster compassion between husband and wife, and make life more religious. There are 2 factors motivating female students of UIN Suska Riau to get married during their lectures, namely motivation from within and outside themselves. The motivation that comes from within the UIN students to get married during the study period is the desire of the senidri, to feel old enough, to feel the need and to have a match. While the motivation that comes from outside of UIN students to get married during the study period is family, social community, campus environment and religion. While the negative impact is difficulty in learning because you don't have time to spare, too much to think about, and some married students can't finish college on time. Obstacles for students in completing college on time are already having children, having difficulty dividing time, and not having free time to study after having children, some other students who do not have children do not have problems in completing college on time. Keywords: Motivation, Student, Married